Breaking The Chains: Fear of Social Judgement and Its Impact on Individual Autonomy in Nepal - Acharya, Sharad (International Journal of Social Sciences and Management, 2025)
The fear of negative evaluation, a psychological phenomenon rooted in social anxiety, significantly impacts individuals' autonomy, self-expression, and decision-making. This paper explores the intricate relationship between the fear of social judgment and personal autonomy, focusing on the cultural and social contexts of Nepal. The methodology is based on subjective analysis and interprets preexisting ideas and concepts using the researcher's critical judgment and comprehension. Drawing on existing literature and a reflective methodology, the study examines how societal norms, cultural expectations, and modern influences, such as social media, exacerbate this fear. In collectivist societies like Nepal, where social conformity and "saving face" hold high value, individuals often suppress personal goals and desires to meet societal standards. This compromises their ability to make autonomous decisions and leads to a loss of true self-expression. The findings reveal that traditional family systems, intergenerational expectations, and digital platforms contribute to heightened social anxiety, further limiting personal freedom. By shedding light on these dynamics, this study underscores the importance of fostering environments that promote individuality and inclusivity. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 99-103.